Diagnostic Challenges and Clinical Implications of Seromucinous Ovarian Neoplasm in Anatomical Dissection: A Case Report: Seromucinous Ovarian Neoplasm: - Velichety, Subhadra Devi; C R, Sirajunnisa Begum; Selvam, Savitha; Jyothi, Ashok Kumar (Biomedical Sciences and Clinical Medicine, 2025)
Ovarian cysts are a common finding, yet their discovery in cadavers during anatomical dissection is relatively rare. Seromucinous ovarian neoplasms represent a distinct subtype of ovarian epithelial tumors, often exhibiting benign behavior. While these tumors typically present with clinical symptoms, their incidental discovery in asymptomatic individuals underscores the diagnostic challenges. The cadaver in this study belonged to a 67-year-old woman with no known medical history of ovarian pathology or related symptoms. Medical records revealed no previous surgeries or interventions related to the reproductive system. The decedent did not report pelvic pain, abnormal uterine bleeding, or palpable abdominal masses during her lifetime. Gross examination revealed an incidental ovarian mass measuring 12x10x5.5 cm, characterized by an enlarged, congested, and cystic external surface. Further examination of the cut surface revealed multiloculated and mucoid material filling the cyst cavity, estimated to be approximately 250 cc in volume. Histopathological examination using hematoxylin and eosin (H&E) stained slides confirmed the diagnosis of a seromucinous ovarian neoplasm. Microscopic analysis depicted a lamellated cyst wall with a single layer of bland mucinous and serous epi-thelium, accompanied by mucoid secretions. The incidental discovery of a seromucinous ovarian neoplasm in this cadaver underscores the diagnostic challenges associated with ovarian pathology, even in the absence of clinical symptoms. This case highlights the importance of thorough anatomical dissections and understanding of the histopathological features of seromucinous tumors essential for accurate diagnosis and appropriate management strategies.